Osteoporosis and genetic influence: a three-generation study. Issue 829 (November 1994) - Kahn, S. A.; Pace, J. E.; Cox, M. L.; Gau, D. W.; Cox, S. A.; Hodkinson, H. M.
Abstract : We have studied 27 triads of mother, daughter and grandmother for possible genetic influence on distal and proximal forearm bone density, measured by single photon absorptiometry. We found a significant correlation of bone density at the proximal forearm between the mothers and grandmothers (r = 0.499, P < 0.01). There was also a weak correlation between proximal forearm bone densities of mothers and daughters (r = 0.327, P < 0.1). Significant correlations were found between the three generations for grip strength, pedometry, height and triceps skinfold thickness. There was also significant correlation between mother and grandmother for alcohol intake. There was no correlation for contraceptive pill use, smoking, dietary calcium intake, body weight or body mass index. The study concludes that, although there are similarities in bone mineral content between the three generations, genetic factors cannot be conclusively proven to be the major determinant of bone density. Lifestyle and environmental factors may have a bearing on achieving the peak bone mass and subsequent development of osteoporosis.